1999
DOI: 10.1111/j.1095-8649.1999.tb00730.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex ratios in offspring of sex‐reversed sea bass and the relationship between growth and phenotypic sex differentiation

Abstract: Groups of sexually undifferentiated sea bass Dicentrarchus labrax were fed with the androgen 17 -methyltestosterone (MT) during sex differentiation. MT treatment increased males from 79 3% in the controls (the usual 3 : 1 male : female sex ratio of cultured sea bass) to 100 0%, implying that in the treated groups one out of each five resulting males was a masculinized female (neomale). Thirteen males from the MT treated groups were taken as the parental generation and their sperm used to individually fertilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 33 publications
(30 reference statements)
4
23
0
Order By: Relevance
“…European sea bass females differentiate earlier, are bigger, and mature later than males (Blázquez et al, 1999; Navarro-Martín et al, 2009a; Díaz et al, 2013). While still sexually undifferentiated, European sea bass gonads can be influenced by environmental abiotic factors or external factors such as sex steroids (Navarro-Martín et al, 2009a), but once sex is determined remains throughout life (Zanuy et al, 2001).…”
Section: Sex-associated Traits In Finfish Aquaculture: Some Relevant mentioning
confidence: 98%
See 2 more Smart Citations
“…European sea bass females differentiate earlier, are bigger, and mature later than males (Blázquez et al, 1999; Navarro-Martín et al, 2009a; Díaz et al, 2013). While still sexually undifferentiated, European sea bass gonads can be influenced by environmental abiotic factors or external factors such as sex steroids (Navarro-Martín et al, 2009a), but once sex is determined remains throughout life (Zanuy et al, 2001).…”
Section: Sex-associated Traits In Finfish Aquaculture: Some Relevant mentioning
confidence: 98%
“…As in most teleosts, sea bass does not show sex chromosomes (Devlin and Nagahama, 2002). Female homogamety (XX) has been ruled out since sex ratios of normal diploid and gynogenetic offspring are equivalent (Felip et al, 2002), and offspring from masculinized females is not female-biased (Blázquez et al, 1999). Other data from hormone-treated fish suggested that male homogamety with environmentally male-biased sex ratio would still be a possibility (Vandeputte et al, 2007).…”
Section: Sex-associated Traits In Finfish Aquaculture: Some Relevant mentioning
confidence: 99%
See 1 more Smart Citation
“…In sea bass, the presence of ovarian tissue in the testes of non-parasitized males (ovo-testis) has been described (Blázquez et al 1999). However, a higher percentage of ovo-testis is found in males infected by S. testicularis than in uninfected ones under the same conditions (A. Sitjà-Bobadilla 1991, unpublished data).…”
Section: Sex Specificity and Sex Reversalmentioning
confidence: 99%
“…7), where sex ratios are the product of both genetic (polygenic sex determination mechanism) (Vandeputte et al 2007) and environmental (temperature) influences (Piferrer et al 2005). In this species, several studies have shown that there is an early association between growth rates and sex (Blázquez et al 1999), with females being among the largest fish and males being among the smallest ones (Blázquez et al 1999; Saillant et al 2001; Vandeputte et al 2007). In addition, sexual growth dimorphism is present at the time of marketing when animals reach 300–400 g (Saillant et al 2001; Navarro-Martín et al 2009a).…”
Section: Environmental Effects On Gene Expressionmentioning
confidence: 99%